Fracture Resistance and Stress Distribution in Endodontically Treated Maxillary Premolars Restored with Composite Resin - Paulo Vin´ıcius Soares, DDS, MS,1 Paulo Ce´ sar Freitas Santos-Filho, DDS, M (Journal of Prosthodontics, 2008)
The aim of this study was to evaluate the effect of endodontic and restorative treatment on the fracture resistance of posterior teeth.